Lithostructural mapping and 3D modeling in a dolomitic marble deposit, Canta-Galo District (Acarape-CE), Borborema Province, Northeastern Brazil - Jonh Maycon Nogueira Azevedo; Sérgio Roberto Bacelar Hühn; Jordan Victor de Oliveira Freire; Irani Cezar Mattos; Igor Moreira da Silva (Brazilian Journal of Geology)
Abstract The definition of geological domains is critical for mineral exploration and has been enhanced through the development of three-dimensional (3D) models. This study focuses on the marble ore bodies in the Canta-Galo Marble District, located in Acarape, Ceará, Brazil, and owned by Geolux Company. Geologically, the Geolux Marble Mine lies within the Borborema Province, specifically in the Northern Domain of the Central Ceará Subdomain. The 3D model was developed using lithostructural mapping, drill hole descriptions and sampling, and an analysis of ore production and mining processes. Data were compiled into a geological database and modeled using the Leapfrog Geo® software. Geolux extracts dolomitic marble, which is then transported to external companies for processing. This manuscript presents a geological model of the marble deposit, based on historical drill holes and geological mapping of the Canta-Galo District. The 3D geochemical and geological interpretation of drill holes reveals the distribution of MgO and SiO2 contents in pure and impure dolomitic marbles. Estimating marble resources will be crucial for medium- to long-term mine planning in this important district of Ceará State.